PENDEKATAN PSIKOLOGI DALAM PENINGKATAN FUNDRAISING ZAKAT - Marwing, Arman (UIN Sayyid Ali Rahmatullah Tulungagung, 2015)
All this time, fundraising for the Foundationof Zakat Administrator (LPZ) keeps some ambivalence. Although fundraising is rated as stimulus of LPZ programs, policies and strategies of professional fundraising-especially the psychological based- get no serious attention. This fact results in many unsuccessful LPZ in realizing the potential of the very large number of zakat in the motherland simultaneously with the increasing of philanthropy awareness of Indonesian muslim. The needs for revamping the fundraising policy on LPZ isin associated with method or approach that should be more count heavily on complexity of the donors psychological aspects include the interaction of decision making process of a donor with demographics aspect and social norms with the result that causes someone decides to donate. Understanding and approaching psychology in fundraising at once are not only encourage the increase of the quantity of donors and donation amount provided, but also raise the position of donors as an object into a subject that also fully and actively involved in running the zakat axiological aspects i.e. functional worship which carry out the empowerment of ummah principle in order to be able to get out of poverty.Keywords: Fundraising, Zakat, Psychological approach